2020
DOI: 10.1101/2020.02.09.940619
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasmin improves oedematous blood-gas barrier by cleaving epithelial sodium channels

Abstract: Background and Purpose: Lung oedema in association with suppressed fibrinolysis is a hallmark of lung injury. We aimed to test whether plasmin cleaves epithelial sodium channels (ENaC) to resolve lung oedema fluid.Experimental Approaches: Human lungs and airway acid-instilled mice were used for analysing fluid resolution. In silico prediction, mutagenesis, Xenopus oocytes, immunoblotting, voltage clamp, mass spectrometry, protein docking, and alveolar fluid clearance were combined for identifying plasmin speci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Serpine1 increased transepithelial permeability. The proteolytic link between the fibrinolytic niche and ENaC proteins has been provided by other groups and us (39)(40)(41)(42). uPA cleaves human gENaC subunits to alter ion transport across the airway epithelium (39).…”
Section: Stem Cell Research and Therapymentioning
confidence: 99%
“…Serpine1 increased transepithelial permeability. The proteolytic link between the fibrinolytic niche and ENaC proteins has been provided by other groups and us (39)(40)(41)(42). uPA cleaves human gENaC subunits to alter ion transport across the airway epithelium (39).…”
Section: Stem Cell Research and Therapymentioning
confidence: 99%
“…Such plasmin-induced cleavage of the ENaC subunits promotes the flow of Na + ions into the epithelial cells, leading to the dehydration of the air-facing surface of the lungs and alveoli, which is normally lined by a thin film of liquid, and hypertension [ 64 ]. Plasmin is a potent protease that cleaves the human γ ENaC subunit at 16 sites, including the cleavage sites of trypsin, chymotrypsin, prostasin, and elastases [ 66 ]. Significant harm is induced by the uncontrolled proteolysis of these proteins, which are highly expressed on epithelial cells, considered as the major pathways for Na + entry, and play important roles in maintaining the proper depth of airway and alveolar lining fluids, the reabsorption of edema fluid in injured lungs, and the regulation of salt retention in the collecting tubules [ 64 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Intrinsic Viral Factorsmentioning
confidence: 99%
“…The SARS-CoV-2 relies on the host cell proteases to cut its S protein in two parts thus forming N-terminal part which recognizes ACE2 receptor and C-terminal part involved in the viral entry which must be further cleaved by furin and/or other furin-like enzymes ( Coutard et al, 2020 ). It has been shown that plasmin is also capable to cleave furin sites ( Zhao et al, 2020 ) and that individuals with elevated plasmin demonstrated higher susceptibility to COVID-19 ( Ji et al, 2020 ). In addition to plasmin, S protein of coronaviruses may be cleaved by other airway proteases such as trypsin-1 and TMPRSS11a ( Ji et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%